AGAMA DI RUANG SOSIAL (Studi Social Capital di Pedesaan Jepara) - MARDIYONO, MARDIYONO (Program Magister Ilmu Politik, Universitas Diponegoro, 2012)
Abstract At first, the religion only as a transcendental issue, private, and now, it has moved into the social space. So, the role of religion is not only taking care of the relationship with God, but religion has become a tool for interaction among member of social groups. Even, religion is presented in a social space eventually gives rise to social norms are adhered to and complied with members of social groups. The norms are adhered has raised confidence among the people, and then formed a Social Capital. This is good news, because the people in Bandungharjo no longer felt to be in silence. Silence in activity. Even further, social capital is formed from a religious activity means the prevention of social segregation. In fact, the days the developments of religious groups were able to make the social space as civil society Bandungharjo. In more convincing religious activity that is able to present the encounter state and society in the social space initiated. Not only that, with high trustÂ religious activities that are capable of forming other values â€‹â€‹than the norm, so that social capital is not just a phenomenon of social labors. Keyword : Religion, Social Space, Trust, Social Capital, Norm, Social Interaction.